5w-3(4x-2w)+3x=

Simple and best practice solution for 5w-3(4x-2w)+3x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5w-3(4x-2w)+3x= equation:


Simplifying
5w + -3(4x + -2w) + 3x = 0

Reorder the terms:
5w + -3(-2w + 4x) + 3x = 0
5w + (-2w * -3 + 4x * -3) + 3x = 0
5w + (6w + -12x) + 3x = 0

Combine like terms: 5w + 6w = 11w
11w + -12x + 3x = 0

Combine like terms: -12x + 3x = -9x
11w + -9x = 0

Solving
11w + -9x = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '9x' to each side of the equation.
11w + -9x + 9x = 0 + 9x

Combine like terms: -9x + 9x = 0
11w + 0 = 0 + 9x
11w = 0 + 9x
Remove the zero:
11w = 9x

Divide each side by '11'.
w = 0.8181818182x

Simplifying
w = 0.8181818182x

See similar equations:

| A=1/2(4.5*h) | | 5(3x-7)-4(x+1)-16x= | | X-7/3 | | 6v-14=3v+7 | | -9+10x= | | .25n+1n=9.8 | | 2x-3=1-x | | 0=x^2-8+3 | | 3xy+4yx= | | 3/2*x=12 | | -8-5x= | | -9+2p= | | x+9=-26 | | (4x-24)+(3x+18)= | | 8x+2x=-10 | | 486=18y+18 | | 17+x+8+x=13 | | 3x-(4x+1)=2x-7 | | 48=4b-8 | | 2(-3a+5)=-4(9+4) | | n^2-6n-4n=0 | | 2k+7c+5c-k= | | -3x+d=-19 | | -3x-5=-2x-4 | | 6+9(7-2)= | | 8+t=5 | | 2y/3-y/4=15 | | -2w=4(w-3) | | -26-6n=4(7n+8) | | (2x^2)+(8x)+(2y^2)=0 | | 3.9v+2.4=0.9v+5.4 | | 8-6t=-16 |

Equations solver categories